1999
DOI: 10.1007/s002130050830
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol induces conditioned place preference in genetically selected alcohol-preferring rats

Abstract: The study of the biological mechanisms of ethanol reward has greatly suffered from problems to obtain ethanol-induced conditioned place preference (CPP) in rats. In the present study, CPP was obtained in genetically selected Marchigian Sardinian alcohol-preferring (msP) rats, derived from Sardinian alcohol-preferring rats, following intragastric (IG) ethanol administration by means of a permanent IG catheter, but not after intraperitoneal (IP) injection or IG gavage. Rats with permanent IG catheter, received I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 23 publications
3
44
1
Order By: Relevance
“…Fidler et al (2004) discusses the role route of administration plays on the development of CPP. Through the implementation of an intragastric route of administration, they support the conclusion that it does not play a role, in contrast with previous work that suggested that the route of administration did play a role in selected lines of rats (Ciccocioppo et al, 1999). Furthermore, it has also been proposed Cunningham and Henderson, 2000) that both CPP, conditioned place aversion, and CTA can be produced in the same animal by the same dose of ethanol simply by varying the timing of administration of the ethanol and the nature of the cues paired with ethanol delivery (gustatory or tactile/environmental).…”
Section: Discussioncontrasting
confidence: 47%
“…Fidler et al (2004) discusses the role route of administration plays on the development of CPP. Through the implementation of an intragastric route of administration, they support the conclusion that it does not play a role, in contrast with previous work that suggested that the route of administration did play a role in selected lines of rats (Ciccocioppo et al, 1999). Furthermore, it has also been proposed Cunningham and Henderson, 2000) that both CPP, conditioned place aversion, and CTA can be produced in the same animal by the same dose of ethanol simply by varying the timing of administration of the ethanol and the nature of the cues paired with ethanol delivery (gustatory or tactile/environmental).…”
Section: Discussioncontrasting
confidence: 47%
“…At first glance, the null effect of distal pre-exposure on ethanol CPP in mice does not appear consistent with several previous studies in rats in which distal pre-exposure has been shown or was alleged to promote the development of ethanol CPP (Reid et al 1985;Gauvin and Holloway 1992;Holloway et al 1992;Bienkowski et al 1995Bienkowski et al , 1996Biala and Kotlinska 1999;Ciccocioppo et al 1999;Gauvin et al 2000). However, interpretation of this apparent species difference is complicated by the fact that most studies using the pre-CS procedure have not found a reliable ethanol-induced CPP in drug-naive rats (Sherman et al 1988;Tzchentke 1998), whereas this outcome is quite common in drug-naive mice (e.g.…”
Section: Place Preferencesupporting
confidence: 36%
“…For example, Marchigian Sardinian alcohol-preferring rats have an obvious preference for the environment associated with alcohol and the alcohol-preferring (P) rats show less aversion than the alcohol non-preferring (NP) rats (Ciccocioppo et al, 1999;Stewart et al, 1996). In addition, P rats and high alcohol drinking (HAD) rats self-administered more alcohol than NP and low alcohol drinking (LAD) rats, respectively, both in fixed and progressive ratio schedule (Ritz et al, 1994;Samson et al, 1998).…”
Section: Discussionmentioning
confidence: 99%